Portal vein resection in pancreatic cancer surgery: risk of thrombosis and radicality determine survival - Hackert, Thilo; Klaiber, Ulla; Hinz, Ulf; Strunk, Susanne; Loos, Martin; Strobel, Oliver; Berchtold, Christoph; Kulu, Yakup; Mehrabi, Arianeb; Müller, Beat P.; Schneider, Martin; Büchler, Markus W. (Annals of surgery, 2023)
Objective: - To evaluate the outcomes of pancreatic cancer [pancreatic ductal adenocarcinoma (PDAC)] surgery with concomitant portal vein resection (PVR), focusing on the PVR type according to the International Study Group of Pancreatic Surgery (ISGPS). - Background: - Surgery offers the only chance for cure in PDAC. PVR is often performed for borderline or locally advanced tumors. - Methods: - Consecutive patients with PDAC operated between January 2006 and January 2018 were included. Clinicopathologic characteristics and outcomes were analyzed and tested for survival prediction. - Results: - Of 2265 PDAC resections, 1571 (69.4%) were standard resections and 694 (30.6%) were resections with PVR, including 149 (21.5%) tangential resections with venorrhaphy (ISGPS type 1), 21 (3.0%) resections with patch reconstruction (type 2), 491 (70.7%) end-to-end anastomoses (type 3), and 33 (4.8%) resections with graft interposition (type 4). The 90-day mortality rate was 2.6% after standard resection and 6.3% after resection with PVR (P<0.0001). Postoperative portal vein thrombosis and pancreas-specific surgical complications most frequently occurred after PVR with graft interposition (21.2% and 48.5%, respectively). In multivariable analysis, age 70 years and above, ASA stages 3/4, increased preoperative serum carbohydrate antigen 19-9, neoadjuvant treatment, total pancreatectomy, PVR, higher UICC stage, and R+ resections were significant negative prognostic factors for overall survival. Radical R0 (>1 mm) resection resulted in 23.3 months of median survival. - Conclusions: - This is the largest single-center, comparative cohort study of PVR in PDAC surgery, showing that postoperative morbidity correlates with the reconstruction type. When radical resection is achieved, thrombosis risk is outweighed by beneficial overall survival times of nearly 2 years.